Development of a toxicity bioassay system using Photobacterium sp. strain mie - Halmi, Mohd Izuan Effendi (2013)
In Malaysia there are about 180 river basins with about 5% of them severely polluted with toxicants. Current costs of instrument-based monitoring prevent regular toxicity monitoring of these polluted rivers. The global trend is using bioassays coupled with instrumental analysis that dramatically reduces the costs of monitoring. Toxicity bioassays using bioluminescent bacteria provide a rapid and sensitive method to monitor the presence of toxicants in the environment and are now globally accepted as the gold standard in environmental monitoring. Unfortunately, the most popular commercial bioassay system uses a bacterial strain that has a low (15oC) and narrow band of optimal working temperature which requires the use of a refrigerated water bath, preventing field work and near real time results. To solve this problem, a novel bioluminescent bacterium Photobacterium sp. strain MIE has been isolated from Indian mackerel, (Rastrelliger kanagurta). The optimal condition for bioluminescence production of this bacterium occurs within a broad temperature range of 24 to 30°C, allowing for easier application in the field. Other optimal luminescence conditions are incubation at pH 5.5-7.5 with 30-50 g/L of tryptone as the nitrogen source, salinity with 15-20 g/L of sodium chloride and 4 g/L of glycerol as the sole carbon source. Experimental results showed that a bioassay system using this bacterium can be used to detect selected toxicants such as heavy metals, xenobiotics and solvents under a broad range of tropical temperature conditions. Photobacterium sp. strain MIE responded sensitively towards mercury, silver, copper, nickel, zinc and chromium with IC50 values (mg/L) of 0.05, 0.12, 0.85, 12.32, 18.72 and 26.02, respectively. In addition, this bacterium could be used to detect the xenobiotics paraformaldehyde, phenol red, cycloheximide, p-nitroaniline, 2,4-dinitrophenol, 2,6-dichloroindophenol, ethanolamine and sodium dodecyl sulfate with IC50 values 20.70, 15.66, 351.40, 64.20, 95.64, 11.34, 629.70 and 55.03 respectively. The IC50 for the solvents hexane, formaldehyde, dimethyl sulfoxide, ammonia, chloroform, tween 80, ethyl acetate, hexanal, methanol are 20.41, 21.10, 28.73, 307.50, 555.30, 591.20, 1687, 3663 and 59,418, respectively. Based on these results, Photobacterium sp strain MIE was sensitive enough to detect various toxicants in the environment. Bioassay using this bacterium is suitable to be applied in the monitoring of toxicants in tropical countries compared to other commercial bioluminescent bacteria which have optimum assay temperatures of less than 25°C. The ability of this bioassay system to detect toxicants was proven in field trials at different polluted locations in Malaysia. The field trial showed promising results with six water samples collected from Juru River and Prai Industrial Estate giving more than 30% inhibitory effect on bioluminescence production. Validation using ICP-OES showed the presence of copper and zinc in these samples that exceeded the limits of permissible pollutants allowed by the Malaysian Department of Environment.